Comparison of impacts of oil infrastructure on grassland songbirds between landscape-scale noise addition and noise removal experiments - Rosa, Patricia; Koper, Nicola (Frontiers in Ecology and Evolution, 2023)
As anthropogenic noise becomes increasingly widespread in natural habitats, noise addition and removal studies have become an important and commonly used method to assess the effects of noise on wildlife. Despite their wide implementation, it is difficult to determine whether the results from these studies translate to natural environments. Oil extraction operations provide a unique opportunity to conduct large-scale natural and experimental noise studies because they emit high-amplitude noise and are subject to interruptions or cessation of operations. We conducted a 6-year study aimed at identifying the effects of different types of oil infrastructure and noise on four species of grassland songbirds in the Canadian prairies. We measured abundance and nesting success of our focal species and compared between a large-scale playback experiment (i.e., noise addition) and in response to real infrastructure (i.e., noise removal). We also conducted an in-depth species analysis of reproductive output, stress, and population structure of an endangered species, Chestnut-collared Longspur (Calcarius ornatus). This multi-species and species-specific approach enabled us to assess noise impacts that may vary among species and for different life-history traits. Overall, our comparative study suggests that noise addition experiments can result in different conclusions regarding the ecological impacts of noise generated from in situ field studies in sites with associated disturbances. While noise clearly impacts birds in many ways, when layered with the many other ecosystem changes associated with real-world oil extraction activity, the effects of noise may be less prominent. As such, caution must be taken when applying results of noise experiments to conservation and management plans and regulations, as effects of noise predicted by lab and field noise addition experiments may simply not be realized under real-world conditions.